Analysis of the Application of Financial Accounting Standards Statement (PSAK) NO 1 in the Financial Report of the Al-Qur'an Education Park (TPQ) Al-Mubarak Balongpoh Sidoarjo - Mahmudah, Mahmudah; Raharjo, Kusuma Adi; Suprihandari, Miya Dewi; Sadiqin, Amin (Journal of International Accounting, Taxation and Information Systems, 2024)
Financial statements provide financial information to see the current condition of a company that is useful for users in the decision-making process. This study aims to analyze the application of PSAK No. 1 regarding the presentation of financial statements prepared by the oleh Taman Pendidikan Al-Quran (TPQ) Al-Mubarak Balongpoh Sidoarjo. The type of research used in this research is descriptive qualitative by describing the theory contained in PSAK No. 1 regarding the presentation of financial statements to the financial statements presented by the ' oleh Taman Pendidikan Al-Quran (TPQ) Al-Mubarak Balongpoh Sidoarjo. The results of this study indicate that the financial statements of the oleh Taman Pendidikan Al-Quran (TPQ) Al-Mubarak Balongpoh Sidoarjo are not fully in accordance with PSAK No. 1, in the financial statements presented by the oleh Taman Pendidikan Al-Quran (TPQ) Al-Mubarak Balongpoh Sidoarjo, it only presents one components of the financial statements, namely the income statement, while the complete financial report according to PSAK No. 1 there are five components of financial statements, namely statements of financial position, income statements, statements of changes in equity, cash flow statements and notes to financial statements.